Awareness among Adult Females about Thyroid Disorder attending Neuro and Allied Clinic, Bhairahawa, Rupandehi, Nepal - Ghimire, Mahesh Raj; Thapa, Sulochana Ghimire; Thapa, Lekhjung; Soti, Binita (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION: Thyroid disorder is common endocrine disorder second to diabetes. With the advancement of laboratory facilities in urban and rural areas, detection rate of thyroid disorder is escalating. Both hyperthyroidism and hypothyroidism can lead to dreaded complication like hypertensive heart disease, coronary arterial disease, arthralgia, severe myalgia, infertility, arrhythmia and many more, so our study helps us to know the awareness amongst a group of population from mid Western part of Nepal. MATERIAL AND METHODS: This is cross sectional descriptive study, conducted in mid Western region of Nepal, among 105 subjects attending Neuro and Allied Clinic, Bhairahawa, Nepal from 15 August, 2019 to 20 August. 2019. RESULTS: Majority 42 (40%) of participants are of age group 36-40 years and are housewives. All are literate and 91 (87%) are married. Most of them 93 (88%) know that it is common in female and one third of them has had their family history positive for this disorder. More than half 37 (53%) of the respondents had inadequate awareness on thyroid disorders whereas 33 (47%) had adequate awareness with mean score 19.9 and 12.4 standard deviation. The maximum score of awareness related question was 42 and minimum 3 obtained by the respondents out of 53. Finally, there is an association between age, education level, occupation status of respondents, respondent’s family members or herself having thyroid disease with awareness level (P ? 0.005), but no association between marital status and awareness level. CONCLUSION: This study reveals majority of people are aware of thyroid disorder but still awareness is inadequate. So, it is mandatory to perform public awareness by NGOs, INGOs and Government sector about thyroid disorder for early diagnosis and to prevent from its complications.